The role of probiotic supplementation in reducing Helicobacter pylori recurrence after classic quadruple therapy - Zhao, Jie; Chen, Jieyun; Wang, Yanqing; Zhu, Chen; Xia, Chenjing; Yang, Wei (Frontiers in Pharmacology, 2025)
BackgroundHelicobacter pylori (H. pylori) infection remains a global public health issue, closely linked to peptic ulcer disease, gastric cancer, and MALT lymphoma. Although classic bismuth-containing quadruple therapy achieves high eradication rates, recurrence after treatment is still a significant concern. Recent evidence suggests that probiotics may support gastrointestinal homeostasis, modulate immune responses, and help prevent H. pylori reinfection. This study aimed to evaluate whether probiotic supplementation reduces H. pylori recurrence following classic quadruple therapy.MethodIn this retrospective cohort study, we analyzed data from 305 adult patients with confirmed H. pylori infection treated at Kunshan Hospital of Traditional Chinese Medicine and Jinxi People’s Hospital of Kunshan between January 2023 and December 2023. All patients received standard quadruple therapy for 14 days. Among them, 127 patients additionally received probiotic supplementation during and for 4 weeks following eradication therapy, while 178 did not. Propensity score matching (1:1) was performed to balance baseline covariates, including age, sex, BMI, smoking status, dietary habits, and prior H. pylori infection history. The primary outcome was H. pylori recurrence within 12 months post-treatment, confirmed by 13C-urea breath test. Secondary outcomes included treatment-related gastrointestinal symptoms, medication adherence, and adverse events.ResultsAfter PSM, 120 matched pairs were analyzed. The recurrence rate of H. pylori was significantly lower in the probiotic group (9.2%) compared to the control group (19.2%) (P = 0.021). Patients in the probiotic group also reported a lower incidence of gastrointestinal discomfort, including bloating and antibiotic-associated diarrhea (P < 0.05), and demonstrated higher treatment adherence (91.7% vs. 83.3%, P = 0.038). No serious adverse events were reported in either group.ConclusionProbiotic supplementation is associated with a reduced risk of H. pylori recurrence after classic quadruple therapy. In addition to improving gastrointestinal tolerance and adherence, probiotics may contribute to maintaining gut microbial balance and enhancing eradication durability. These findings support the integration of probiotics as an adjunct to standard therapy. Further randomized controlled trials are needed to confirm efficacy and identify optimal probiotic formulations and duration.